2019
DOI: 10.1182/blood-2019-126622
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Myeloid Leukemia in Adolescents and Young Adults: A Single Institute Experience

Abstract: Background and Objectives: CML is a myeloproliferative neoplasm characterized by the dysregulated production and uncontrolled proliferation of mature and maturing granulocytes with fairly normal differentiation. It mainly affects adults, and is rarely seen in children. The average age at diagnosis of CML is around 64 years. There are few studies describing CML in adolescents and young adults. In Qatar we have one of the largest cohorts of adolescents and young adults with CML. This study aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…TKIs act by interfering with the interaction between the BCR-ABL oncoprotein and adenosine triphosphate, thereby blocking the proliferation of the malignant clone. There are currently three TKIs that are approved by the Food and Drug Administration (FDA) for the first-line treatment of chronic phase CML: imatinib, dasatinib, and nilotinib [4].…”
Section: Introductionmentioning
confidence: 99%
“…TKIs act by interfering with the interaction between the BCR-ABL oncoprotein and adenosine triphosphate, thereby blocking the proliferation of the malignant clone. There are currently three TKIs that are approved by the Food and Drug Administration (FDA) for the first-line treatment of chronic phase CML: imatinib, dasatinib, and nilotinib [4].…”
Section: Introductionmentioning
confidence: 99%
“…Whether age per se is a risk factor is unknown. Despite the average age at diagnosis of CML being around 64 years, one cohort study concluded that CML presented more aggressively in adolescents and young adults as compared to older patients; however, there was no difference in outcome [10].Obesity could play a role, since in one study [11] mean age at diagnosis was lower in obese patients compared with the control group (39.0 vs. 42.2). Obese patients had a lower WBC count and a higher Hb level at diagnosis (mean WBC 153.9 vs. 193.0; mean Hb 11.4 vs. 10.3), and obese patients showed a better response to treatment and were less likely to need a switch to tyrosine kinase inhibitors due to failure of treatment [11].…”
Section: Discussion/conclusionmentioning
confidence: 96%
“…Whether age per se is a risk factor is unknown. Despite the average age at diagnosis of CML being around 64 years, one cohort study concluded that CML presented more aggressively in adolescents and young adults as compared to older patients; however, there was no difference in outcome [ 10 ]. Obesity could play a role, since in one study [ 11 ] mean age at diagnosis was lower in obese patients compared with the control group (39.0 vs. 42.2).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Chronic leukemias include lymphocytic and myelogenous leukemias, which carries an overall more benign course than acute leukemias and occurs typically in the adult population 3 . Chronic myeloid/ myelogenous leukemia (CML) is one of the MPNs and accounts for 15% of newly diagnosed leukemia in adults; it is characterized by the presence of BCR‐ABL1 fusion oncogene; this rearrangement is known as the Philadelphia chromosome 4 . CML can range from an asymptomatic course, which accounts for almost 50% of cases diagnosed in the United States, to a wide array of signs and symptoms, including fatigue, weight loss, fever, abdominal discomfort, and many other manifestations 4 .…”
Section: Introductionmentioning
confidence: 99%